PENGARUH KEKERASAN VERBAL TERHADAP SELF EFFICACY SISWA KELAS V SEKOLAH DASAR DI BANDUNG - Yulianti Lumban Gaol, - (2022)
Self-efficacy is the self-confidence possessed by elementary school-aged children to organize and complete certain tasks in achieving the desired results. The development of self-efficacy in elementary school-aged children is certainly supported through the role of parents through positive communication between parents and children. But not all parents do this. Verbal abuse committed by parents can affect the development of self-efficacy of elementary school-aged children. This study aims to determine the effect of verbal abuse on self-efficacy of fifth grade elementary school students in Bandung. This research uses correlational methods. With a sample of fifth grade students at SDN 007 Cipaganti and SDN 200 Leuwi Panjang. The instrument used is a questionnaire of verbal abuse and self efficacy. The results of this study indicate the existence of verbal abuse experienced by students by parents verbally. As well as the high and low self-efficacy fifth grade students. The relationship between verbal abuse by parents verbally on self-efficacy of fifth grade elementary school students in Bandung is related to r table (0.20276) and r arithmetic (0.437), it can be interpreted that there is a strong relationship between verbal abuse and self-efficacy variables self-efficacy. The magnitude of the effect obtained through a simple regression test (0.191) or 19.10%. The more often parents do verbal abuse against children, the lower the child's self-efficacy. However, the more parents communicate positively with their children, the higher the child's self-efficacy.